THE INFLUENCE OF PROFITABILITY, LEVERAGE, AND COMPANY SIZE ON COMPANY VALUE (Case Study of Food and Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange for the 2018-2021 Period) - Lidiana Simanjuntak; Timbul Hamonangan Simanjuntak; Carolina F. Sembiring (Fundamental Management Journal, 2024)
These studies aims to determine Effects of Pro fitabilities, Leveraged, and Companies Size on Companies Values (In Foods and Beverages Sub-Sector listed on Indonesian Stock Exchanges for periodic 2018 to 2021) both partial and simultaneously, samples in these studies were obtaining use purposive sampling techniques, so that 15 samples were obtaining with researched periodic 2018 to 2021. Data types use secondaries data, data analyst use classical assumption tested and hypothesis tested use panel data regresion analyst use Eviews 12 tool. researched model using in analyst is use chow tested and hausman tested with Random effects model method. results of these studies show that partial hypothetical calculation of Profitabilities variable has a significant effects on Companies Value. Laverage and Companies Size have no effects on Companies Value. and for simultaneous tested results obtaining F calculate > F table = 0.006646 < 0.05 means testeding Profitabilities (X1), Leveraged (X2) and Companies Size (X3) have a simultaneous effects on Companies Values (Y). From results of these studies, Coeficient of Determination (R2) with a values of 0.151482 means that 15.14% of disclosures are explaining by Profitabilities, Leveraged and Companies Size. Keywords: Profitability, Leverage and company Size